2011
DOI: 10.2174/1874285801105010021
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Commercially Available Alpha-Amylase Compounds to Inhibit and Remove Staphylococcus aureus Biofilms

Abstract: Staphylococcus aureus, a versatile human pathogen, is commonly associated with medical device infections. Its capacity to establish and maintain these infections is thought to be related to its ability to form adherent biofilms. In this study, commercially available α-amylase compounds from various biological sources were evaluated for their ability to reduce and prevent biofilm formation of several S. aureus isolates. Our data demonstrates that α-amylase compounds can rapidly detach biofilms of S. aureus, as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
36
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(44 citation statements)
references
References 65 publications
4
36
1
Order By: Relevance
“…In this way, clinicians would be able to administer the enzymes to any patient presenting with a biofilm infection, regardless of the causative microorganisms, and have a reasonable expectation that the therapy will be effective. ␣-Amylase and cellulase are two inexpensive, commercially available GHs that target common linkages found in the EPS made by many different species of bacteria, and multiple studies have shown that they can inhibit and disrupt the preformed in vitro biofilms of a variety of bacterial species (22)(23)(24)(25)(26).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this way, clinicians would be able to administer the enzymes to any patient presenting with a biofilm infection, regardless of the causative microorganisms, and have a reasonable expectation that the therapy will be effective. ␣-Amylase and cellulase are two inexpensive, commercially available GHs that target common linkages found in the EPS made by many different species of bacteria, and multiple studies have shown that they can inhibit and disrupt the preformed in vitro biofilms of a variety of bacterial species (22)(23)(24)(25)(26).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that cellulase inhibits biofilm growth by Burkholderia cepacia and Pseudomonas aeruginosa on various abiotic surfaces commonly used in medical devices (22,23). Similarly, ␣-amylase, a GH that acts by cleaving the ␣-1,4 straight-chain linkage, has been previously shown to both inhibit biofilm formation and disrupt preformed biofilms of Vibrio cholerae, Staphylococcus aureus and P. aeruginosa in vitro (24)(25)(26). In this study, we aimed to hydrolyze the polysaccharides produced by S. aureus and P. aeruginosa in dual-species polymicrobial biofilms by targeting a pair of highly conserved glycosidic linkages.…”
mentioning
confidence: 99%
“…Previous studies described several compounds that have the potential to destabilize the structures, damage the biofilm, or facilitate the penetration of antibiotics, including dispersin B, DNase I, and ␣-amylase (52)(53)(54). Dispersin B hydrolyzes the poly-N-acetylglucosamine surface polysaccharide within the biofilm matrix of many bacteria, including S. aureus (53), while DNase I degrades extracellular DNA, which serves as a matrix adhesion molecule in biofilms produced by most bacteria (54).…”
Section: Discussionmentioning
confidence: 99%
“…DNase I, on the other hand, detached preformed S. aureus biofilms but not S. epidermidis biofilms (53). Similarly, ␣-amylase, an enzyme found in human pancreatic juice and saliva, rapidly detached S. aureus biofilms and dissociated S. aureus aggregates in liquid culture but had no effect on S. epidermidis biofilms (52). Compared with the reported performance of these compounds, NxtSc-G5 appears to be efficacious in penetrating biofilms formed by S. aureus and P. aeruginosa in vitro and in vivo and eliminating the microorganisms within the biofilms.…”
Section: Discussionmentioning
confidence: 99%
“…Use of α-amylase was effective in detaching biofilms for some bacterial species ( Staphylococcus aureus ) but not others ( S. epidermidis ) [27]. Lyase in combination with gentamycin reduced viable counts of Pseudomonas aeruginosa by 2-3 log 10 units [28], while lactonase increased penetration of ciprofloxacin and gentamycin [29].…”
Section: Antibiofilm Treatmentsmentioning
confidence: 99%